International Bank Portfolios: Short- and Long-Run Responses to the Business Cycle - Sven Blank; Claudia M. Buch (Institut für Angewandte Wirtschaftsforschung (IAW), 2007)
International bank portfolios constitute a large component of international country portfolios. Yet, their response to macroeconomic conditions and their impact on the international transmission of business cycles developments remains largely unexplored. We use a novel dataset on banks? international portfolios to answer three questions. First, what are the long-run determinants of banks? international portfolios? Second, how do banks? international portfolios adjust to short-run macroeconomic developments? Third, does the speed of adjustment change with the degree of financial integration? We provide evidence of significant long-run cointegration relationships between cross-border assets and liabilities of banks and key macroeconomic variables. Both, the long-run determinants of banks? international portfolios as well as the short-run dynamics show a significant degree of heterogeneity across countries and, to some extent, over time. Gravitytype variables help explaining differences in the speed of adjustment to new equilibria.
Keywords: F32; F34; F42; 330; international bank portfolios; macroeconomic developments; transmission channels; Internationale Bank; Bilanzstrukturmanagement; Portfolio-Management; International; Makroökonomischer Einfluss; Konjunkturzusammenhang; Welt